A study of the effects of thin dyke intrusions on mudrock - Connolly, Jacqueline (Trinity College (Dublin, Ireland). Department of Geology, 2003)
The aim of this work is to examine the thermal response of mudrock to the short lived heating event induced by dyke intrusion. The work examines five Carboniferous mudrock horizons, intruded by Tertiary olivine tholeiitic dykes. Two of the mudrock sample horizons (named CK and CQ) were collected from the Carrickleck Quarry in the Kingscourt Outlier and are cut by a 1.5m wide dyke. The other three mudrock horizons (named BC, cMd and NSD) were collected from the north Antrim coast, near Ballycastle, and are cut by a 4m wide dyke. The mudrock horizons were sampled at up to 30 positions over 7-80m from the dyke, with sampling density increasing within dm from the dyke margin. Samples were processed and analysed for vitrinite reflectance, spore colour, spore fluorescence, palynofacies, clay mineralogy, illite crystallite size, and bulk chemistry. In addition a numerical model was used to estimate the temperatures reached in the two dyke aureoles. The stratigraphic age of the Ballycastle rocks was determined using palynology. Vitrinite reflectance results show background values of c. 1% Rr. However as the dyke is approached the values increase exponentially to c. 3.6% Rr at Carrickleck and 5.5% Rr at Ballycastle before dropping to c. 3% Rr at Carrickleck and 3.8% Rr at Ballycastle within c.20cm from the contact. However, background VR values from coal lenses in the cMd horizon and at the Gobb Colliery section, c. 2km away were as low as 0.5% Rf. Spore colour index (TAI) increases steadily as the dyke is approached, from a background level of around 2 rising to 5 at the contact.
Keywords: Geology, Ph.D.; Ph.D. Trinity College Dublin